Effect of a cannabinoid agonist on gastrointestinal transit and postprandial satiation in healthy human subjects: a randomized, placebo‐controlled study - Esfandyari, T.; Camilleri, M.; Ferber, I.; Burton, D.; Baxter, K.; Zinsmeister, A. R. (Neurogastroenterology and motility, 2006)
Cannabinoid receptor (CBR) stimulation inhibits motility and increases food intake in rodents. Effects of CBR stimulation in human gastrointestinal (GI) tract are unclear. We compared effects of dronabinol (DRO) and placebo (PLA) on GI transit, gastric volume and satiation in humans. In a double‐blind, randomized study, 30 healthy volunteers were randomly assigned to DRO 5 mg b.i.d. or PLA for three doses. We measured GI functions noninvasively: day 0, Ensure® satiation test to measure maximum tolerated volume (MTV) and 30‐min post‐Ensure® symptoms; day 1, scintigraphic transit (111In‐egg meal) and fasting and postprandial gastric volume (99Tcm‐SPECT); day 2, 24‐h colonic transit and repeat satiation test. ancova was used to compare treatment groups with gender, age, and, for the satiation test, the baseline MTV, as covariates. A log‐rank test was used to assess treatment effects on gastric emptying. Planned sample size had 80% power to detect 25–30% differences in primary end points. There was an overall retardation of gastric emptying with DRO (P = 0.018); this was more pronounced in females (P = 0.011), than in males (P = 0.184). No significant treatment differences were detected for gastric volumes, MTV, post‐Ensure® symptoms, small bowel and colonic transit. Fasting gastric volume was greater in males receiving DRO compared with PLA (238 ± 17 vs 185 ± 16, P = 0.04). DRO retards gastric emptying in humans; effects are gender‐related. Dronabinol also increases fasting gastric volumes in males.